1979
DOI: 10.1002/ps.2780100606
|View full text |Cite
|
Sign up to set email alerts
|

The antifungal activity of alkyl benzimidazol‐2‐ylcarbamates and related compounds

Abstract: The fungistatic activity against Penicillium digitatum and Diplodia natalensis decreased slightly in ascending a homologous series of alkyl esters of benzimidazol‐2‐ylcarbamic acid from the methyl ester (carbendazim) to the pentyl ester; the hexyl and octyl esters were inactive. 2‐(Acylamino)benzimidazoles were slightly less active than the analogous alkyl benzimidazol‐2‐ylcarbamates. Introduction of a methylene bridge between the benzimidazole ring and the 2‐methoxycarbonylamino group abolished antifungal act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1983
1983
1989
1989

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…), and they must be explained with a structure/activity studies of carbendazim analogues reported by Eckert and Rahm (1979). Imazalil has a different biochemical mode of action and structure (Eckert and Rahm, 1979), showing the most important effects on apple ripeness in both cultivars studied.…”
Section: Nsmentioning
confidence: 99%
See 1 more Smart Citation
“…), and they must be explained with a structure/activity studies of carbendazim analogues reported by Eckert and Rahm (1979). Imazalil has a different biochemical mode of action and structure (Eckert and Rahm, 1979), showing the most important effects on apple ripeness in both cultivars studied.…”
Section: Nsmentioning
confidence: 99%
“…The different biochemical mode of action of each product produced different effects in the apple quality and ripeness param-' eters (Brix degrees, acidity, total sugars, etc. ), and they must be explained with a structure/activity studies of carbendazim analogues reported by Eckert and Rahm (1979). Imazalil has a different biochemical mode of action and structure (Eckert and Rahm, 1979), showing the most important effects on apple ripeness in both cultivars studied.…”
Section: Nsmentioning
confidence: 99%